Perlindungan Hukum Tenaga Kesehatan dari Penyerangan Kelompok Kriminal Bersenjata - Mohammad Imam Mubarok; Sutrisno (Jurnal Risalah Hukum, 2022)
Indonesia is a country rich in ethnicity, language and culture spread from Sabang to Merauke, with a population of 273.5 million. For this reason, a rule of law is needed to regulate and protect every plural society in Indonesia, especially in the field of human rights. This research uses normative juridical research. carry out law enforcement in the field of human rights and related to legal protection for medical personnel who are victims of the KKB attack which is linked to Law No. 26/2000 and regulations related to legal protection and human rights enforcement. The results of the study show that the legal process for the KKB attack case against health workers is still hampered by the implementation of regulations that have not worked properly. The continued impact of this condition will cause human rights violations to occur which in the end will also hamper the fulfillment of human rights for the people of Papua at large. The Indonesian government needs to further encourage institutions working in the field of human rights to make various efforts to carry out their functions more optimally.